Chest Press Exercises With Different Stability Requirements Result in Similar Muscle Damage Recovery in Resistance-Trained Men. Issue 1 (January 2017) - Ferreira, Diogo V.; Ferreira-Júnior, João B.; Soares, Saulo R.S.; Cadore, Eduardo L.; Izquierdo, Mikel; Brown, Lee E.; Bottaro, Martim
Abstract : Abstract: Ferreira, DV, Ferreira-Júnior, JB, Soares, SRS, Cadore, EL, Izquierdo, M, Brown, LE, and Bottaro, M. Chest press exercises with different stability requirements result in similar muscle damage recovery in resistance trained men. J Strength Cond Res 31(1): 71–79, 2017—This study investigated the time course of 96 hours of muscle recovery after 3 different chest press exercises with different stability requirements in resistance-trained men. Twenty-seven men (23.5 ± 3.8 years) were randomly assigned to one of the 3 groups: (a) Smith machine bench press; (b) barbell bench press; or (c) dumbbell bench press. Participants performed 8 sets of 10 repetition maximum with 2 minutes rest between sets. Muscle thickness, peak torque (PT), and soreness were measured pre, post, 24, 48, 72, and 96 hours after exercise. There were no differences in the time course of PT or muscle thickness values of the pectoralis major ( p = 0.98 and p = 0.91, respectively) or elbow extensors ( p = 0.07 and p = 0.86, respectively) between groups. Muscle soreness of the pectoralis major was also not different between groups ( p > 0.05). However, the Smith machine and barbell groups recovered from triceps brachii muscle soreness by 72 hours after exercise ( p > 0.05), whereas the dumbbell group did not present any triceps brachii muscle soreness after exercise ( p > 0.05). In conclusion, resistance-trained men experience similar muscle damage recovery after Smith machine, barbell, and dumbbell chest press exercise. However, muscle soreness of the elbow extensors takes a longer time to recover after using a barbell chest press exercise.